National contributions to global ecosystem values. Issue 5 (1st April 2019) - Coristine, Laura E.; Colla, Sheila; Bennett, Nathan; Carlsson, Anja M.; Davy, Christina; Davies, Kimberley T.A.; Favaro, Brett; Flockhart, D.T. Tyler; Fraser, Kevin; Orihel, Diane; Otto, Sarah P.; Palen, Wendy; et al.
Abstract: Current conservation templates prioritize biogeographic regions with high intensity ecosystem values, such as exceptional species richness or threat. Intensity‐based targets are an important consideration in global efforts, but they do not capture all available opportunities to conserve ecosystem values, including those that accrue in low intensity over large areas. We assess six globally‐significant ecosystem values—intact wilderness, freshwater availability, productive marine environments, breeding habitat for migratory wildlife, soil carbon storage, and latitudinal potential for range shift in the face of climate change—to highlight opportunities for high‐impact broadly‐distributed contributions to global conservation. Nations can serve as a cohesive block of policy that can profoundly influence conservation outcomes. Contributions to global ecosystem values that exceed what is predicted by a nation's area alone, can give rise to countries with the capacity to act as 'conservation superpowers', such as Canada and Russia. For these conservation superpowers, a relatively small number of national policies can have environmental repercussions for the rest of the world.